(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: Improving Student Learning Outcomes of Christian Religious Learning Through the Implementation of Expository Learning Strategies in Class VII-2 of SMP Negeri 1 Patumbak. Class VI student learning outcomes on material longing to beg for forgiveness after using Expository Learning Strategy as the first action (cycle 1) obtained an average of 67.70% or with 60% completeness and 40% error. Class VII-2 student learning outcomes on material longing to beg for forgiveness after the improvement of Expository Learning Strategies as repetition of teaching (cycle 2) obtain student learning outcomes an average of 80.20%, or in other words 100% completeness rate and error 0 %. There is an increase in student learning outcomes material longing to beg for forgiveness after using Expository Learning Strategies by 40%. Keywords: Learning Outcomes, Longing To Ask For Forgiveness, Expository Abstrak: Meningkatkan Hasil Belajar Siswa Pelajaran Agama Kristen Melalui Penerapan Strategi Belajar Ekspositori Di Kelas VII-2 SMP Negeri 1 Patumbak. Hasil belajar siswa Kelas VI pada materi kerinduan untuk memohon ampun setelah digunakan Strategi Belajar Ekspositori sebagai tindakan pertama (siklus 1) memperoleh hasil rata-rata 67,70% atau dengan perincian ketuntasan 60% dan kesalahan 40%. Hasil belajar siswa Kelas VII-2 pada materi kerinduan untuk memohon ampun setelah dilakuan perbaikan Strategi Belajar Ekspositori sebagai pengulangan pengajaran (siklus 2) memperoleh hasil belajar siswa rata-rata menjadi 80,20%, atau dengan kata lain tingkat ketuntasan 100% dan kesalahan 0%. Terdapat peningkatan hasil belajar siswa materi kerinduan untuk memohon ampun setelah digunakan Strategi Belajar Ekspositori sebesar 40%. Kata kunci: Hasil Belajar, Kerinduan Untuk Memohon Ampun, Ekspositori